Desempenho agronômico, qualidade da fibra e viabilidade econômica do algodão naturalmente colorido submetido a doses de fósforo no semiárido brasileiro - Santos, Manoel Galdino dos (Universidade Federal Rural do Semi-Árido, 2021)
The cultivation of naturally colored fiber cotton occurs mainly in the Brazilian Semiarid region. Its cultivation has great potential for the region, as its fibers are more valued in comparison to white fiber, dispensing with the chemical dyeing that causes residues and it also reduces the consumption of water in the process. However, in general, soils have low levels of phosphorus (P), affecting productivity, fiber quality and profitability of the colored cotton production system in the Semiarid region. Given the above, the objective of this work was to analyze the influence of P on agronomic performance, fiber quality and economic viability of naturally colored cotton cultivars, under irrigation, in the conditions of the Brazilian Semiarid. Two experiments were carried out in the field, in the years 2017 and 2018, at the Rafael Fernandes Experimental Farm of the Federal Rural University of the Semi-Arid in the municipality of Mossoró-RN. The experimental design was in completely randomized blocks with treatments arranged in plots subdivided with four replications. In the main plot, the doses of P (0; 60; 120; 180 and 240 kg ha-1 of P2O5) were allocated, and in the subplots the naturally colored cotton cultivars (BRS Rubi, BRS Safira, BRS Topázio and BRS Verde) were allocated. In general, fertilization with P provided better performance, quality and economic viability of colored cotton in the Semiarid conditions. In the first agricultural harvest, cotton cultivars achieved the best performance. The highest seed cotton yields were: 2,420.01 kg ha-1 (BRS Rubi, 60 kg ha-1 of P2O5); 2,460.76 kg ha-1 (BRS Safira, 240 kg ha-1 of P2O5); 3,086,90 kg ha-1 (BRS Topázio, 226.90 kg ha-1 of P2O5) and 2,352.60 kg ha-1 (BRS Verde, 198.73 kg ha-1 of P2O5). Doses of 120; 34.68; 180 and 80.86 kg ha-1 of P2O5 provided the longest fiber length in the cultivars BRS Rubi (21.57 mm), BRS Safira (22.00 mm), BRS Topázio (29.82 mm) and BRS Verde (26,00 mm), respectively. The highest fiber strengths were obtained at doses of 0 kg ha-1 (BRS Rubi); 180 kg ha-1 (BRS Safira); 180 kg ha-1 (BRS Topázio) and 240 kg ha-1 (BRS Green) of P2O5. The highest net incomes achieved were: R$ 2,050.29 ha-1 (BRS Rubi); R$ 949.14 ha-1 (BRS Safira); R$ 2,860.29 ha-1 (BRS Topázio) and R$ 848.76 ha-1 (BRS Verde) in doses of 60; 198.01; 188.65 and 157.09 kg ha-1 of P2O5, respectively. The cultivar BRS Topázio obtained better yields, fiber quality and profitability
Keywords: Gossypium hirsutum L.; Cultivares; Produtividade; Resistência da fibra; Lucratividade; Gossypium hirsutum L.; Cultivars; Productivity; Fiber strength; Profitability; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA